Analisis Pengaruh Kualitas Auditor dan Kualitas Laporan Keuangan Terhadap Opini Audit Periode Tahun 2008–20011 (Studi Empiris pada Perusahaan yang Tergabung dalam Lq 45 Di Bei Periode 1 Agustus 2008 – 31 Januari 20011) - Gantino, Rilla (Jurnal Ekonomi : Journal of Economic, 2013)
AbstractThis study aims to determine whether there is influence between Quality Auditor and Quality of Financial Statement of Audit Opinion. Financial Report provides information for the parties concerned are expected to give a reflection of the company's financial condition without any actual earnings manipulation practices that may mislead users of financial statements. Audit is expected to restrict the practice of earnings management and help maintain and enhance public confidence to the financial statements. In this study assessed the quality of auditors' Big four auditors grouping with non big four and the quality of financial reports can be viewed on the basis of presence or absence of actions that intentionally flattening profits made by companies judged by Eckel index. Data analysis method used is to use statistical methods that is by binary logistic regression. Results of the study is that there are several affiliated companies in 45 LQ 1 August 2008-31 period January 2011 to do the leveling profits. The results of the first test of the alternative hypothesis accepted means that the quality of auditors and quality of financial reporting is a significant simultaneously on the audit opinion. The second alternative acceptable Hipotesisi means that the quality of financial reporting significantly affect the audit opinion. As for the third alternative hypothesis is rejected it means that the quality of auditors do not have a significant impact on the audit opinion.Keyword: auditor quality, financial report quality, audit opinion